Development of smart fruit basket for pineapple harvesting - Mezlan, Nurul Shahida; Zainal Abidin, Emilia; Karuppiah, Karmegam; Rasdi, Irniza; Syed Ismail, Sharifah Norkhadijah; Ismail, Noor Hassim (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Pineapple harvesting work contributes to the reporting of musculoskeletal symptoms (MSS) and ergonomic risks. Pineapples are harvested manually in some parts of Malaysia using rattan baskets and workers are exposed to excessive bending, pain and discomfort. This intervention study developed and tested a prototype of an ergonomic harvesting basket to potentially reduce discomfort and physiological workload during a simulation of harvesting activity. Methods: The development and testing of improved harvesting basket was performed in laboratory and workshop. The improved basket had adjustable cushion straps, foam back pad and an opening for unloading of fruits. Harvesting was simulated using improved and existing basket by human subjects and questionnaires were used to assess discomfort. Physiological workload was assessed by heart rate and energy expenditure. Results: A total of 12 male respondents with average age of 22.4 (2.2) years participated in harvesting simulation. Discomfort as measured in Likert scale (mean (standard deviation) for improved basket 4.13 (6.1) vs existing basket 12.26 (11.2); p<0.05) was significantly reduced. Average heart rate (94.13 beats/min vs 89.05 beats/min) and energy expenditure (6 kJ/min vs 5 kJ/min) improved. Conclusion: The use of improved basket was linked to reduction of discomfort and overall workload. Improving design of agricultural manual tools may be able to improve health of workers and prevent MSS. Future fabrication of the improved basket using lightweight materials has potential to be expanded into plantation sectors not limited to pineapples in Malaysia and across Asia.